Digital transformation, digital gap and modernisation of higher education - Titarenko, Larissa G. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The purpose of the article is to compare the levels of digital knowledge and competencies of three groups living in Minsk (students, specialists with higher education, and citizens as a whole). The task is to identify possible digital gaps between these groups in the context of a pandemic. Special focus is made on the impact of the students’ level of digital literacy on the prospects for further modernisation of higher education. The main factors contributing to the growth of digital knowledge and competencies of the above-mentioned groups of citizens are identified. The digital literacy of these three groups are compared; digital gap between the younger generations and older urban residents are shown. The scientific significance of the study lies in demonstrating the dependence of the effectiveness of digital social transformation and digital modernisation of higher education on the level of digital literacy of these three groups. It is shown that the pandemic stimulated the development of distance learning and, indirectly, digital modernisation in higher education.
Keywords: digital transformation; modernisation of higher education; pandemic; digital knowledge and competences; students; professionals; city dwellers; information-communication technologies; distance learning